2005
DOI: 10.1515/cclm.2005.006
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of fibrinolysis parameters during myocardial revascularization according to type of procedure

Abstract: The aim of the study was to assess the effect of cardiothoracic surgery on the dynamics of plasminogen, D-dimers and plasminogen activator inhibitor (PAI-I) during the first 24 h after surgery. The study included 14 patients operated with (on-pump) and 14 without (off-pump) the use of extracorporeal circulation (ECC). Blood sampling was carried out on induction of anesthesia (timepoint 1), on introduction of heparin (point 2) and protamine (point 3), at the end of surgery (point 4), and the next morning (point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A comparison of minimally invasive closed circuit extracorporeal circulation with on-pump and off-pump bypass showed less perioperative activation of coagulation and fibrinolysis in patients undergoing off-pump surgery compared with that seen in patients undergoing on-pump surgery [21,22]. Other smaller studies have suggested comparable rather than disparate activation of the fibrinolytic system by on-pump and off-pump surgery [23,24]. Activation of fibrinolysis has been seen with extracorporeal circulation used during the course of valve replacement surgery [25].…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of minimally invasive closed circuit extracorporeal circulation with on-pump and off-pump bypass showed less perioperative activation of coagulation and fibrinolysis in patients undergoing off-pump surgery compared with that seen in patients undergoing on-pump surgery [21,22]. Other smaller studies have suggested comparable rather than disparate activation of the fibrinolytic system by on-pump and off-pump surgery [23,24]. Activation of fibrinolysis has been seen with extracorporeal circulation used during the course of valve replacement surgery [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, according to the authors knowledge, this is the first study assessing the relationship between the dynamics of D-dimer levels increase and the time to artery recanalization in ischemic stroke. Only Zivković et al [22] monitored D-dimer levels dynamics during myocardial revascularization according to type of procedure.…”
Section: Discussionmentioning
confidence: 99%